Organic Phosphorus Scavenging Supports Efficient Growth of Diazotrophic Cyanobacteria Under Phosphate Depletion - Rabouille, Sophie; Tournier, Lauralie; Duhamel, Solange; Claquin, Pascal; Crispi, Olivier; Talec, Amélie; Landolfi, Angela; Oschlies, Andreas (Frontiers in Microbiology, 2022)
Considering the reported significant diazotrophic activities in open-ocean regions where primary production is strongly limited by phosphate, we explored the ability of diazotrophs to use other sources of phosphorus to alleviate the phosphate depletion. We tested the actual efficiency of the open-ocean, N2-fixer Crocosphaera watsonii to grow on organic phosphorus as the sole P source, and observed how the P source affects the cellular C, N and P composition. We obtained equivalently growth efficiencies on AMP and DL-α-glycerophosphate as compared with identical cultures grown on phosphate, and survival of the population on a phytic acid. Our results show that Crocosphaera cannot use all phosphomonoesters with the same efficiency, but it can grow without phosphate, provided that usable DOP and sufficient light energy are available. Also, results point out that organic phosphorus uptake is not proportional to alkaline phosphatase activity, demonstrating that the latter is not a suitable proxy to estimate DOP-based growth efficiencies of organisms, whether in culture experiments or in the natural environment. The growth parameters obtained, as a function of the P source, will be critical to improve and calibrate mathematical models of diazotrophic growth and the distribution of nitrogen fixation in the global ocean.